Filmwise condensation of steam on pin fin arrays fabricated by selective laser melting - Ho, Jin Yao (2020)
In this study, nine vertical flat plates of pin fin arrays were fabricated by selective laser melting to investigate the possible enhancements of external condensation. These specimens are cylindrical pin fins of the same fin diameter of 300 μm but are of different fin heights (l) and fin pitches (p) from 300 μm to 900 μm. Experiments were conducted in a condensation chamber with near quiescent vapor to simulate free-convection condensation. The aim is to investigate the effects of fin pitch and fin height on the condensation heat transfer performance of the surfaces. The results of this study show that the increase in fin height and the decrease in fin pitch lead to a systematic increase in the condensation heat flux (q''). At the same fin pitch, the increase in fin height from 600 μm to 900 μm resulted in a more significant increase in q'' as compared to the increase in fin height from 300 μm to 600 μm. On the other hand, at the same fin height, a larger increase in q'' is observed when the fin pitch is reduced from 900 μm to 600 μm as compared to the reduction in fin pitch from 600 μm to 300 μm. It can be deduced that increasing the fin height enables the fins to protrude out of the thick condensate film and increases the effective heat transfer area of the surfaces. However, when the fin density is large, it impedes the condensate drainage path and limits the enhancement in q''. The enhancement factor (η), which is the ratio of the average condensation heat flux of a pin fin surface to that of a plain surface, was computed for each specimen. The highest η value of 1.72 was achieved with the specimen of 900 μm fin height and 300 μm fin pitch. Finally, a relationship between η and the dimensionless fin pitch-to-height ratio (p/l) is proposed.